Strong Perpendicular Anisotropy and Anisotropic Landé Factor in Bismuth-Doped Thulium Garnet Thin Films - Zhang, Xiuye; Jin, Lichuan; Zhang, Dainan; Liu, Bo; Meng, Hao; Zhang, Lei; Zhong, Zhiyong; Tang, Xiaoli (Frontiers in Materials, 2022)
With the development of spintronics, garnet films with perpendicular magnetic anisotropy (PMA) have been attracting the attention of researchers for decades. In this work, bismuth-doped thulium iron garnet (Tm2BiFe5O12, TmBiIG) films of multiple thickness having strong PMA effect were fabricated on substituted Gd3Ga5O12 (sGGG) (111) substrates by pulsed laser deposition (PLD) technique. Crystallographic characterization and magnetic properties of TmBiIG films were investigated using high-resolution scanning transmission electron microscopy, X-ray diffraction, vibrating sample magnetometry and broadband ferromagnetic resonance (FMR), respectively. A high perpendicular anisotropic field of H⊥=4445±7.5 Oe in 10 nm thick film and H⊥=4582±7.7 Oe in 30 nm thick film at room temperature were obtained and analyzed in details. Surprisingly, an additional spin-wave mode was observed in the in-plane FMR spectra. The discrepancy between in-plane and the out-of-plane Landé g-factors, established a correlation with the PMA effect in the TmBiIG films. The Landé g-factor of the TmBiIG films is much lower than that of free electrons indicating that the strong spin-orbit coupling is caused by the Tm and Bi heavy elements. The Gilbert damping factor α changes from 0.007 to 0.012 in various thicknesses TmBiIG films.